1999
DOI: 10.1161/01.cir.99.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Acute and Chronic Coronary Stenting in Humans

Abstract: Morphology after coronary stenting demonstrates early thrombus formation and acute inflammation followed by neointimal growth. Medial injury and lipid core penetration by struts result in increased inflammation. Neointima increases as the ratio of stent area to reference lumen area increases. Deployment strategies that reduce medial damage and avoid stent oversizing may lower the frequency of in-stent restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
482
2
16

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 787 publications
(528 citation statements)
references
References 16 publications
(17 reference statements)
20
482
2
16
Order By: Relevance
“…7,22,23,32,35,46,77,81,82,86 The mechanical impact of the investigated stents was evaluated in terms of the equivalent von Mises stress (ES) distribution predicted in the artery wall. The ES is calculated as follows:…”
Section: Analysis Of Balloon-expandable Coronary Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,22,23,32,35,46,77,81,82,86 The mechanical impact of the investigated stents was evaluated in terms of the equivalent von Mises stress (ES) distribution predicted in the artery wall. The ES is calculated as follows:…”
Section: Analysis Of Balloon-expandable Coronary Stentsmentioning
confidence: 99%
“…Over the past two decades, several clinical studies have identified strong correlations between neointimal hyperplasia following coronary stent deployment and both stent-induced arterial injury 7,22,23,32,35,46,77,81,82,86 and altered vessel hemodynamics. 6,17,18,20,21,52,71,79,88 In light of these observations, a significant body of research has been carried out in this area.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Injury stimulates medial smooth muscle cells to undergo proliferation, dedifferentiate with expression of fetal phenotype proteins, and migrate into the intima. The morphologic changes in ultrastructure entail both hyperplasia of the migrant smooth muscle cells and enhanced deposition of extracellular matrix proteins and glycosoaminoglycans, [4][5][6] leading to thickening of the intimal layer and narrowing of the arterial lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Le traumatisme artériel provoqué par l'implantation d'un stent est très différent de celui qui suit une angioplastie au ballonnet [7]: les barreaux métalliques dilacèrent profondément la paroi artérielle, non seulement au niveau de la plaque d'athérosclérose et de son centre lipidique, mais aussi de la média sous-jacente, avec une relation quasi linéaire entre la sévérité du traumatisme et l'épaississement intimal qu'il engendre (voir Encadré). L'examen de prélèvements post-mortem montre une réaction inflammatoire riche en macrophages et en lymphocytes T, présente à tous les stades de développement de la néointima et prédominant dans les premières semaines [7].…”
Section: Revues Dossier Techniqueunclassified